Witness-in-communion: a theology of existence to essence during the pandemic - Bell, Charles J. M. (Theology, 2021)
The past months of pandemic have laid down a number of challenges to both the practices of the Christian faith and the theology that underpins many of these practices. This article seeks to discern a method of doing theology that can be responsive to these changed circumstances and which might help cast new light on entrenched positions in the Church. Such a theology takes experienced phenomena seriously, recognizing the key role a lived reality plays in a sacramental faith. It situates the importance of this experience in the biblical mandate to the Christian to be a witness, albeit one grounded in and inhabiting the community of the faithful. This grounding tests experience in the fire of Scripture and living tradition to continually refine the essential nature of what can be said to be. In doing so, we enter ever more into the mystery of a God made incarnate and of God’s created order.